Pengaruh Metode Fabrikasi Terhadap Ketahanan Impak Komposit Sandwich Serat Karbon - M. Faiz Ardiansyah; Firman Yasa Utama (CV. SINAR HOWUHOWU, 2026)
Carbon fiber sandwich composites are lightweight materials with high potential for structural applications because they offer a good combination of strength and stiffness. However, their mechanical properties and durability are influenced by the fabrication methods used. This study aims to analyze the effects of the hand lay-up, vacuum infusion, and hybrid vacuum infusion–hand lay-up methods on the impact strength of carbon fiber sandwich composites with a Lantor Coremat core. The study employed an experimental method with a quantitative approach. Specimens were fabricated using carbon fiber, epoxy resin, and Lantor Coremat, and then tested using the Charpy impact method in accordance with ASTM D6110. The data obtained consisted of impact energy (EI) and impact value (HI), which were subsequently analyzed using quantitative descriptive statistics based on the average values for each fabrication method variation. The research results show that the hybrid method produced the highest impact resistance, with an average impact energy of 7.50 J and an impact value of 0.157 J/mm², followed by the vacuum infusion method at 5.35 J and 0.113 J/mm², and the hand lay-up method at 2.22 J and 0.047 J/mm². These results indicate that combining the vacuum infusion and hand lay-up processes improves resin impregnation quality and reduces internal defects in the composite. Thus, the hybrid method has the potential to serve as an effective fabrication alternative for producing sandwich composites with improved impact resistance for engineering applications requiring lightweight yet strong material.